Distributed vibration sensor with a high strain dynamic range by harmonics analysis. (April 2023) - Chen, Mengmeng; Zhu, Runze; Luo, Junxian; Masoudi, Ali; Chen, Ye; Brambilla, Gilberto; Xu, Fei
Highlights: Based on the research results of this paper, the strain dynamic range of the DVS can be improved by analyzing the harmonic numbers in the vibration response spectrum. The vibration amplitude of the DVS can be quantitatively measured with a strain resolution of 0.78 με for each additional harmonic. The system and data analysis can significantly improve the strain dynamic range in comparison with traditional DVS based on the intensity or polarization information. The proposed scheme of the DVS is very simple and it does not need two acousto-optic modulators (AOMs) or electro-optic modulators (EOMs), or a narrow line width laser, or a high-speed data acquisition (DAQ) card, it is simple and low-cost. Abstract: Distributed vibration sensors (DVSs) have important applications in industrial production. A large strain dynamic range is very important for DVSs, but difficult to achieve as it often requires a complex sensing system or cumbersome data processing. This study shows that the strain dynamic range of the DVS can be improved by analyzing the harmonic numbers in the vibration response spectrum, and the vibration amplitude can be quantitatively measured with a strain resolution of 0.78 με for each additional harmonic. The system and data analysis method can significantly improve the strain dynamic range in comparison with traditional DVS based on the intensity or polarization information.